(untitled) (Journal Of Educational and Psychological Researches, 2014)
The researcher identified the objective of this research Do you know the impact of the way to solve problems in the achievement of the students in the fourth grade prep Islamic Education, and the researcher has identified the limits of the search, and the terms contained in the title researched and then offered the researcher previous studies relate to the subject studied, introduced Studies in Arab and foreign countries dealt with how to solve problems, the researcher identified the methodology discussed public represented by experimental method, and the sample consisted of two groups, one experimental and the other officer, and worked on the set of variables that may affect the results between the two groups in vkavot changers task, the results reached through statistical means necessary, in the light of the findings of the researcher from the results of the way to solve problems in the article about the collection made a number of conclusions focused on the effectiveness of this method in Education, and made a number of recommendations for those with their own hands the decision to invest in this effective method of education, and made a number of proposals by a number of anwanat complement to search in the current study